Perspektif Hakim terhadap Penerapan Hukum Adat dalam Penyelesaian Perkara Pidana di Pengadilan Negeri Padangsidimpuan - Marwan Busyro; Bandaharo Saifuddin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The background of this research aims to determine and analyze judges' perspectives on the application of customary law in resolving criminal cases at the Padangsidimpuan District Court. Customary law is an unwritten legal system that exists and develops within society and is often used as a consideration in deciding cases related to local values ​​and cultural wisdom. In the context of Padangsidimpuan society, which still strongly upholds customs and traditions, customary law often serves as a means of resolving social conflicts before they enter the formal legal realm. The research method used is empirical juridical, with data collection techniques through direct interviews with judges and document studies of several relevant court decisions. The results indicate that most judges at the Padangsidimpuan District Court view customary law as a complementary instrument to positive law, particularly in minor criminal cases with social and familial dimensions. Judges strive to consider customary values ​​to achieve substantive justice, without neglecting the principle of legality and statutory provisions. However, the application of customary law cannot replace positive law in its entirety; rather, it serves as a moral and social value that strengthens the community's sense of justice.